Strategi Pengembangan Ekowisata Bahari Pulau Tolandono Kabupaten Wakatobi - Ode Mansyur, La; Nasrun, Nasrun; Normayasari, Normayasari; Harudin, Harudin; Ikhsan, Nur; Isman, Khairudin; Sahari, Sariamin; Kusuma Admaja, Alfi; Musrianton, Muhammad; Ferlin, Akhmatul; Utami, Dewi; Hamka, Eddy; Amijaya Husain, Suharta (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2025)
This study aims to analyze strategies for developing marine ecotourism in Tolandono Island, Wakatobi Regency, Southeast Sulawesi, to support environmental sustainability and improve the welfare of local communities. A qualitative descriptive method with a SWOT (Strengths, Weaknesses, Opportunities, Threats) approach was employed to identify potentials and challenges in ecotourism development. Data were collected through observations, semi-structured interviews with 55 respondents, and focus group discussions (FGD) involving tourism business actors, local communities, tourists, and relevant institutions. The findings reveal that Tolandono Island possesses high marine biodiversity and conservation status, despite challenges such as inadequate infrastructure, low capacity of local human resources, and threats to marine ecosystems from destructive activities and climate change. Four main strategies were formulated: 1) technology-based promotion and development of tourism facilities (SO); 2) human resource training, institutional strengthening, and infrastructure improvement (WO); 3) resource management to address environmental threats (ST); and 4) conservation education and livelihood diversification (WT). The implementation of these strategies is projected to increase tourist visits by 20% annually, contribute up to IDR 2 billion per year to the local economy, and reduce marine ecosystem damage by 25%. This study highlights the importance of collaboration between the government, local communities, and stakeholders to ensure sustainable community-based ecotourism in Tolandono Island.